Conjugated Polymers: Optical Toolbox for Bioimaging and Cancer Therapy. Issue 43 (12th September 2021) - Wei, Jinchao; Liu, Ying; Yu, Jie; Chen, Ling; Luo, Mai; Yang, Lele; Li, Peng; Li, Shengliang; Zhang, Xiao‐Hong
Abstract: Conjugated polymers (CPs) are capable of coordinating the electron coupling phenomenon to bestow powerful optoelectronic features. The light‐harvesting and light‐amplifying properties of CPs are extensively used in figuring out the biomedical issues with special emphasis on accurate diagnosis, effective treatment, and precise theranostics. This review summarizes the recent progress of CP materials in bioimaging, cancer therapeutics, and introduces the design strategies by rationally tuning the optical properties. The recent advances of CPs in bioimaging applications are first summarized and the challenges to clear the future directions of CPs in the respective area are discussed. In the following sections, the focus is on the burgeoning applications of CPs in phototherapy of the tumor, and illustrates the underlying photo‐transforming mechanism for further molecular designing. Besides, the recent progress in the CPs‐assistant drug therapy, mainly including drug delivery, gene therapeutic, the optical‐activated reversion of tumor resistance, and synergistic therapy has also been discussed elaborately. In the end, the potential challenges and future developments of CPs on cancer diagnosis and therapy are also illuminated for the improvement of optical functionalization and the promotion of clinical translation. Abstract : This review summarizes the recent progress of conjugated polymer (CP) materials in bioimaging, cancer therapeutics, and introduces design strategies by rationally tuning the optical properties. Challenges and future developments of CPs on cancer diagnosis and therapy are also illuminated to boost next development of CPs design and biomedical applications, and improving optical functionalization for the promotion of clinical translation.